Increasing the conductivity of aluminium high-pressure die casting alloy AlSi9Cu3Fe (226D) by Sr modification of eutectic and intermetallic phases - Feyer, Felix; Weigand, Michael; Randelzhofer, Peter; Körner, Carolin (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2025)
High-pressure die casting alloys are currently optimized to have an excellent castability and to fulfil the mechanical properties of the demanded parts. In general the conductivity of these alloys decreases from the efforts to improve the mechanical properties and the castability. Although new components in the mobility and communication sector demand alloys with improved conductivity. Focus of the work is the evaluation of influence of modification on the conductivity and mechanical properties of high-pressure die casting alloy AlSi9Cu3Fe. A new Cu-die design with vacuum assistance which mimics the microstructure of high-pressure die castings on lab scale for high throughput investigation was used. The combination of modification of the Si phase and intermetallic phases morphology and distribution collectively influences the properties of the alloy. The extent of modification is connected to the level of alloying elements and Sr content present. The conductivity is increased by more than 10
Keywords: Al alloys; Si modification; Conductivity; Hardness; High throughput